Islam dan Nasionalisme: Studi tentang Peranan Hizbullah dalam Mempertahankan Negara Kesatuan Republik Indonesia - Derani, Saidun; Ats Tsaqofi, Waki; Rokhim, Minatur; Fahmi, Nurrizal (UIN Syarif Hidayatullah Jakarta, 2022)
Laskar Hezbollah which consists of scholars and students have a major contribution in maintaining the Unitary State of the Republic of Indonesia (NKRI). However, the role of Hezbollah in the historiography of Indonesian history has not yet received an adequate place in the struggle to defend the Unitary State of the Republic of Indonesia when compared to the role of the army and other national parties. This study was conducted to answer the above problems so that it can enrich the writing of Indonesian National HistoryThis study uses a historical research methodology with a sociological and theological approach. The sources in the study will be presented in a descriptive analytical manner, both primary and secondary. Then in looking at the problem, the theory or concept of collective behavior is used in the context of nationalism and patriotism.There is also a finding of this study that based on facts and field data Hezbollah has a major contribution in defending the Unitary State of the Republic of Indonesia. Thus, this study wants to complement the reference works of Indonesian history that have not placed the role of ulama and santri in significantly defending the Unitary Republic of Indonesia. Second, this study wants to show that the ulama and santri have a high love for their country so that their nationalism and patriotism cannot be doubted. In other words, this study wants to strengthen the study conducted by Musa (2001) which concluded that there was a very close relationship between religion and nationalism. Third, national unity from various elements of the nation became an important factor in a revolution so that Indonesia succeeded in getting its sovereignty from the hands of the Dutch in late 1949 and early 1950. In this context, the role of Muslims cannot be ignored in fulfilling the independence of the Republic of Indonesia.